Growth Response of Red Spinach (Amaranthus Gangeticus) by Giving Cow Manure and Rice Husk Ash. - Yudi Triyanto; Fitra Syawal Harahap, SP. M.Agr (Scopus ID : 57209419315); Khairul Rizal; Hilwa Walida; Amos Poplius Sihombing (JURNAL AGROPLASMA, 2020)
The increase in market demand red spinach (Amaranthus Gangeticus) makes the prospects very promising less than optimal for the growth of red spinach (Amaranthus Gangeticus) because soil fertility is low so that the provision of organic material can improve soil fertility through the improvement of the physical, chemical, and biological soil so that it can support the growth of red spinach. This study aims to determine the dose of manure, the dosage of rice husk ash as well as the interaction of dosage that is optimal for the growth and yield of red spinach.this research was conducted experimental farm of the faculty of science and technology with a height of 28 meters above sea level Labuhanbatu district in March to October 2020. Research design using group factorial consisting of two factors. The first factor, namely the granting of cow manure (L) with three levels, namely : L0 = 0 ton/ha (control) L1 = 2 ton/ha, equivalent to 200 g/m2 (the recommended dose), L2 = 4 ton/ha, equivalent to 400 g/m2, L3 = 6 ton/ha, equivalent to 600 g/m2. The second factor, rice husk ash (A) consists of 4 levels, namely : A0 = 0 ton/ha (control), A1 = 1 ton/ha equivalent to 50 g/m2 (the recommended dose), A2 = 1.5 tons/ha, equivalent to 75 g/m2.The Parameters measured were plant height (cm), number of leaves (strands), Weight per Plant Sample (g). The results showed that the administration of cow manure 4 ton/ha, equivalent to 400 g/m2 can increase plant height, leaf number, and weight per Plant of amaranth red. The provision of 1.5 tons/ha, equivalent to 75 g/m2 can increase plant height, the number of leaves plant red spinach (Amaranthus Gangeticus).Keywords: Rice Husk Ash, Red Spinach, Cow Manure, Plant Growth